The Effect of Transformational Leadership and Orgaanizational Commitment with Job Satisfaction as Intervening Variable on Organizational Citizenship Behavior for the Environment (OCBE) – Case Study of Employees in Agency of Labor, Transmigration and Energy Special Capital Region of Jakarta - Sihombing, Olifia N.; Iqbal, M. Ali (Indonesian Journal of Business Analytics, 2024)
The objective of this study is to investigate how transformational leadership, organizational commitment and job satisfaction as intervening variable would influence Organizational Citizenship Behavior for the Environment (OCBE) in Agency of Labor, Transmigration and Energy Special Capital Region of Jakarta. The method used in the study is quantitative method and the whole population is used as sample or known as non-probability sampling. Population of the study is civil servants with two-year minimum experience with a total of 93 people. The data was analysed with Structural Equation Model (SEM) using SmartPLS 4. The results show that transformational leadership influence job satisfaction, organizational commitment influence job satisfaction, transformational leadership influence OCBE, job satisfaction influence OCBE, organizational commitment has positive and significant impact on OCBE, transformational leadership through job satisfaction as intervening variable influence OCBE, organizational commitment through job satisfaction as intervening variable influence OCBE.